Indonesian EFL prospective teachers’ intention to perform (ITP) in the English language: a preliminary study - Saiful, Jepri Ali; Widodo, Pratomo (Penerbit Universiti Kebangsaan Malaysia, 2019)
The study of behavioural intention in social psychology has been shifting towards language learning and education. However, the state and determinants of behavioural intention in language learning performance remains under explored, particularly in the context of Indonesian EFL teachers. This study aims to investigate the nature of the behavioural intention of prospective Indonesian EFL teachers to perform in the English language, otherwise known as their intention to perform (ITP) and elicit the construct factors affecting the ITP. This study involved 76 participants taken randomly from the population of 85 fourth year undergraduate students of the English Education Department in one Indonesian State University. Data were collected using valid and reliable questionnaires and were analysed with descriptive statistics and single and multiple regression tests. Before the regression tests, prerequisite tests of normality, homoscedasticity, linearity, and multicollinearity were administered. This study revealed that prospective Indonesian EFL teachers had extremely high intention to perform in the English language. Those zealous intentions had two antecedents: one’s beliefs or feelings toward the English language – and of the feelings predominated the beliefs. Importantly, this study showed that collective judgement, targeting both beliefs and feelings about the language, could provide the impetus for prospective Indonesian EFL teachers to perform in the English language, more than partial judgement did. Consequently, to increase the willingness of learners to perform the target language, teachers must optimise the learners’ target language beliefs and feelings uniformly and concurrently.